Interference as an Origin of the Peaked Noise in Accreting X-Ray Binaries - Veledina A. (IOP, 2022)
We propose a physical model for the peaked noise in the X-ray power density spectra of accreting X-ray binaries. We interpret its appearance as an interference of two Comptonization continua: one coming from the upscattering of seed photons from the cold thin disk and the other fed by the synchrotron emission of the hot flow. Variations of both X-ray components are caused by fluctuations in mass accretion rate, but there is a delay between them corresponding to the propagation timescale from the disk Comptonization radius to the region of synchrotron Comptonization. If the disk and synchrotron Comptonization are correlated, the humps in the power spectra are harmonically related and the dips between them appear at frequencies related as odd numbers 1:3:5. If they are anti-correlated, the humps are related as 1:3:5, but the dips are harmonically related. Similar structures are expected to be observed in accreting neutron star binaries and supermassive black holes. The delay can be easily recovered from the frequency of peaked noise and further used to constrain the combination of the viscosity parameter and disk height-to-radius ratio α(H/R)2 of the accretion flow. We model multi-peak power spectra of black hole X-ray binaries GX 339-4 and XTE J1748-288 to constrain these parameters.